Populations dynamics in Northern Eurasian forests: a long-term perspective from Northeast Asia. (21st May 2020) - Uchiyama, Junzo; Gillam, J. Christopher; Savelyev, Alexander; Ning, Chao
Abstract: Abstract: The 'Northern Eurasian Greenbelt' (NEG) is the northern forest zone stretching from the Japanese Archipelago to Northern Europe. The NEG has created highly productive biomes for humanity to exploit since the end of the Pleistocene. This research explores how the ecological conditions in northern Eurasia contributed to and affected human migrations and cultural trajectories by synthesizing the complimentary viewpoints of environmental archaeology, Geographic Information Science (GIS), genetics and linguistics. First, the environmental archaeology perspective raises the possibility that the NEG functioned as a vessel fostering people to develop diverse cultures and engage in extensive cross-cultural exchanges. Second, geographical analysis of genomic data on mitochondrial DNA using GIS reveals the high probability that population dynamics in the southeastern NEG promoted the peopling of the Americas at the end of the Pleistocene. Finally, a linguistic examination of environmental- and landscape-related vocabulary of the proto-Turkic language groups enables the outline of their original cultural landscape and natural conditions, demonstrating significant cultural spheres, i.e. from southern Siberia to eastern Inner Mongolia during Neolithization. All of these results combine to suggest that the ecological complex in the southern edge of the NEG in northeast Asia played a significant role in peopling across the continents during prehistory.